Neck strength and self-reported neck dysfunction: What is the impact of a season of Rugby Union? - Salmon, D. M.; Sullivan, S. J.; Handcock, P.; Rehrer, N.; Niven, B. (The Journal of Sports Medicine and Physical Fitness, 2018)
BACKGROUND: Neck strength has been reported to reduce the incidence of concussions and neck injuries. However, little is known about how neck strength changes over a playing season. The aim of this study was to understand the impact a 20-week rugby season has on neck strength, neck pain (NP) and neck stiffness (NS) in a cohort of rugby players, relative to a non-contact control group. METHODS: This prospective cohort study employed a fixed-frame dynamometer to measure neck strength in a simulated contact posture in rugby players (N.=32) and controls (N.=15). During each assessment, participants performed a single maximal voluntary contraction in extension, flexion, left (LtFlx) and right lateral flexion (RtFlx). To quantify neck dysfunction, "current," "average," and "worst" NP and NS were measured using visual analogue scales. RESULTS: Post-season improvements (35.3-59.1 N) in neck strength were observed for the forwards for all measured directions (P<0.01), and were significant when compared to controls. For the backs, improvements were seen in extension, flexion and LtFlx (P=0.01-0.05), with only extension (29.8 N) and flexion (35.14 N) remaining significant when contrasted against the controls. The controls` neck strength remained unchanged over the season. Despite improvements in peak force, NP increased (all three measures) for the forwards (P=0.01-0.04), while only current (P=0.03) and worst NP (P=0.04) increased for the backs. Unexpectedly, NS remained unchanged for the forwards, while backs reported increases for all three measures (P=0.01-0.02). CONCLUSIONS: A season of rugby resulted in neck strength adaptations in the rugby players. Despite these improvements, increased levels of NP and NS were reported.